TINDAK LANJUT KEBIJAKAN PERMENDIKBUD RISTEK NOMOR 30 TAHUN 2021 DALAM UPAYA PENCEGAHAN DAN PENANGANAN KEKERASAN SEKSUAL DI UNIVERSITAS DIPONEGORO - Irawan, Syifa Salsabila; Astuti, puji -; -, Supratiwi - (Journal of Politic and Government Studies, 2024)
The implementation of the policy for preventing and handling sexual violence within Diponegoro University is carried out with reference to Permendikbud Ristek No. 30 of 2021 concerning Prevention and Handling of Sexual Violence in Higher Education Environments. The implementation of this policy was carried out because of concerns about cases of sexual violence that occurred in universities. In this case, universities must be free from sexual violence so that the rights of the academic community can be fulfilled and the educational process can run optimally. This research aims to determine the follow-up to the implementation of policies for preventing and handling sexual violence within Diponegoro University using the theory of public policy implementation models put forward by Charles O. Jones (1984). The research approach used is post-positivist with qualitative data collection techniques through in-depth interviews as primary data and literature studies as secondary data, and the analysis techniques used are qualitative. The results of this research indicate that the implementation of policies for preventing and handling sexual violence within Diponegoro University by referring to Permendikbud Ristek No. 30 of 2021 concerning Prevention and Handling of Sexual Violence in Higher Education Environments has been implemented with the record that there is a lack of quantity and quality of human resources to meet organizational dimensions. However, the implementation of this policy has not been implemented in fulfilling the interpretation dimension which consists of a lack of socialization. The final dimension implemented in the implementation of policies for preventing and handling sexual violence at Diponegoro University is the application dimension